INCREASING TAX COMPLIANCE THROUGH STRENGTHENING CAPACITY OF EDUCATION SECTOR FOR EXPORT ORIENTED SMES HANDICRAFT FIELD IN EAST JAVA INDONESIA - Mukhlis, Imam; Utomo, Sugeng Hadi; Soesetyo, Yuli (European Scientific Journal, ESJ, 2014)
This study aims to identify the factors that may affect tax compliance from SME entrepreneurs. In addition, this study also aims to design a tax compliance model through tax education for SME entrepreneurs. The method of data analysis used in this study was done through qualitative and quantitative approaches. The object in this study is the SME entrepreneurs of handicraft field districts/cities in East Java. The results of this study lead to the conclusion that tax compliance can be built through tax fairness formed through the life of the entrepreneurs themselves. Then, tax fairness can be built through increasing the undersanding about taxes for the SME entepreneur. This understanding is dealing with the benefits associated with tax rates and tax penalties, tax type, tax administration, and the tax service. In improving the understanding of taxation, it is necessary to give education for the SME businesses primarily through socialization in the form of formal or informal. Based on the results of data analysis, it can be concluded that basically the SME entrepreneurs is able to understand their tax obligations when there is an aspect of fairness and tax benefits that can be received in real terms by SME entepreneurs. The relevant suggestions are needed to do educational activities through dissemination of taxation and tax benefits for the continuity of SMEs entrepreneurs in East Java, Indonesia.